Successful CD19 chimeric antigen receptor T-cell therapy following autologous stem cell transplantation in a secondary central nervous system lymphoma patient with COVID-19 infection: a case report and literature review - Wang, Xiaoning; Ren, Juan; Wang, Yuqi; Luo, Minna; Li, Jing; He, Pengcheng (Frontiers in Oncology, 2025)
This paper reported a 64-year-old, secondary central nervous system lymphoma (sCNSL) patient with COVID-19 infection during CD19 chimeric antigen receptor T-cell (CAR-T) therapy following autologous stem cell transplantation (ASCT). Our findings demonstrate that the combination of ASCT and CAR-T for sCNSL may be feasible, even for SARS-CoV-2-positive immunocompromised lymphoma patients.